Comparison of three-dimensional printing guides and double-layer guide plates in accurate bracket placement - Yue Zhang; Chunhao Yang; Yanfeng Li; Dong Xia; Tingting Shi; Changjian Li (BMC, 2020)
Abstract Background In the current study, we aimed to evaluate the accuracy of indirect bonding by either three-dimensional (3D) printing guides or double-layer guide plates. The results may serve as a clinical reference for bracket placements. Methods In total, 140 teeth were collected and arranged into five pairs of full dentition. The marking points were labeled on the buccal/labial surface of the crown in these orthodontic study models. (1) 3D printing guide: A digital profile was generated using an intraoral scanner. Two types of indirect bonding guide, namely the whole denture type and the single tooth type, were designed with the 3Shape TRIOS® Standard intraoral scanner and fabricated using 3D printing technology. (2) Double-layer guide plate: A working model was obtained by replicating the experimental models, and the double-layer guide plate was then made of the inner layer soft film (1.0 mm thickness) and the outer layer hard film (0.6 mm or 0.8 mm thickness). Brackets were transferred from working models to study models by the indirect bonding trays. We measured and analyzed the distance between marking points and bracket placement. Statistical analysis was done using SPSS 20.0 software. The accuracy of indirect bonding between 3D printing guide and double-layer guide plate was compared using paired t-test. Results According to our data, there was a significant difference between the 0.6 mm group and 0.8 mm group when the brackets were indirectly adhered using double-layer guide plates (p = 0.036). However, no statistical significance in bracket positioning accuracy was revealed between two types of 3D printing guide (p = 0.078), as well as between the 3D printing guide group and the 0.6 mm double-layer guide plate group (p = 0.069). Conclusions When applying double-layer guide plates for indirect bonding, the 0.6 mm group is more accurate than the 0.8 mm group. When utilizing 3D printing guides for indirect bonding, whole denture type is more accessible than single tooth type but with no significant difference in accuracy. The accuracy of indirect bonding is comparable when using 3D printing guides (whole denture type) and double-layer guide plates (0.6 mm).